Procedure Recording And Billing Receivables : Case Study on CV. Putra Baja Krakatau - Esti Utami Pratiwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Politeknik Piksi Input Serang, 2022)
Purpose - In facing market competition, companies can actively build relationships or partner to entity other so that more easy for To do sale and get profit. On transaction credit, recording as well as billing accounts receivable is a vital aspect : payment accounts receivable outside the time limit will hinder current required company cash to support whole activities, other than that without good recording of accounts receivable, accounts receivable that have been circulated to customers are not is known amount by accurate. Company must pro-active in doing billing and recording accounts receivable so that no occur things which give rise to n further loss in the future. Purpose of research this is for analyze billing problem accounts receivable and form billing procedure and recording receivables. Design/methodology/approach - Method used in research this is method study descriptive qualitative with collection observational data and interview with party which related with study Finding - Results from study this is formation alternative billing procedure receivables to partners by giving warnings if payments are made outside the due date, as well as recording procedures accounts receivable using Microsoft Excel adapted from the book Accounting System by Mulyadi. Receivables beyond the maturity of CV. Putra Baja Krakatau caused by xiieriod internal and external. Constraints faced by CV. Son of Krakatoa Steel in To do recording accounts receivable is because lack of employee in company.. Originality - This study illustrates that the application and management of accounts receivable at MSMEs is still not optimal, so it requires guidance and training in the field of accounting so as to produce financial reports in accordance with applicable financial standards..